Incorporation of graphene oxide/titanium dioxide with different polymer materials and its effects on methylene blue dye rejection and antifouling ability - Suriani Abu Bakar (Tanjung Malim, 2023)
Incorporation of graphene oxide/titanium dioxide with different polymer materials and its effects on methylene blue dye rejection and antifouling ability by Suriani Abu Bakar